Field Efficacy of Dactylaria higginsii as a Bioherbicide for the Control of Purple Nutsedge (Cyperus rotundus) - Kadir, Jugah; Charudattan, R.; Stall, William M.; Brecke, Barry J. (Cambridge University Press, 2000)
An isolate of the fungus Dactylaria higginsii obtained from purple nutsedge in Florida was highly pathogenic to Cyperus spp. The potential of this isolate as a bioherbicide was field tested in natural populations of purple nutsedge in Gainesville and Jay, FL. The fungus was applied in 0.5% Metamucil® as a carrier, and the treatments were: carrier only, 105 conidia/ml carrier, and 106 conidia/ml carrier. Treatments were applied as single, double, or triple postemergence (POST) sprays at biweekly intervals. The disease and secondary infections developed in about 5 and 15 d after inoculation, respectively, killing most of the infected leaves. All weed growth parameters and disease progress rates were affected by inoculum dosage and inoculation frequencies. Three inoculations, each at 106 conidia/ml, provided effective control of purple nutsedge compared to a single inoculation, as measured by shoot dry weight, tuber numbers, and tuber dry weight. Higher rates of disease progress and disease levels, defined by the area under the disease progress curve (AUDPC), occurred with three inoculations at 106 conidia/ml. Disease progress was slower and the level of weed control was lower at 105 conidia/ml compared to the higher inoculum level. Three applications of 106 conidia/ml provided >90% nutsedge control. Dactylaria higginsii appears to be an effective bioherbicide candidate deserving further development for commercial use.